Challenges for numeracy awareness in the 21st century: making visible the invisible - Díez-Palomar, Javier; Ramis-Salas, Mimar; Močnik, Ivan; Simonič, Marijana; Hoogland, Kees (Frontiers in Education, 2023)
Introduction The contemporary scientific literature indicates that numeracy is a multifaceted concept. The ongoing societal and technological transformations underscore the imperative to re-evaluate the attributes characterizing a numerate individual and the strategic initiatives that policymakers should devise and implement to ensure that individuals are not marginalized from participation in public and private domains due to their lack of numeracy proficiency. Numerous empirical investigations on numeracy consistently affirm its pivotal role in enabling individuals to engage autonomously across diverse contexts within their daily lives. However, numeracy’s fundamental role has often been neglected in our societies. The present study scrutinizes the overarching challenges associated with numeracy, particularly emphasizing the challenges regarding healthcare, finance, and the critical utilization and interpretation of data awareness. Methods A two-phase research framework was adopted to address this inquiry. A comprehensive literature review was conducted to discern the prevalent challenges regarding numeracy awareness. Subsequently, two illustrative case studies were undertaken in Slovenia and Spain to contrast and deliberate upon the insights derived from the literature review. Qualitative research methods were employed to engage in a nuanced exploration of the gathered data. Results This empirical analysis deduced guidelines aimed at enhancing awareness and ameliorating some of these challenges. Discussion and Conclusion We conclude that making visible the awareness that adults already have about numeracy in aspects of their lives, such as finance, health, or the use and critical interpretation of data, can give policymakers and curriculum developers clues to design effective numeracy programs to address the multifaceted challenges confronting contemporary society, both in the immediate and foreseeable future.